PENGARUH LAYANAN KONSELING KELOMPOK TEKNIK BEHAVIOR CONTRACT UNTUK MENINGKATKAN KEDISIPLINAN BELAJAR PADA SISWA KELAS XI IPS SMA NEGERI 2 KOTA BENGKULU - Barbarenta Breskila; Yessy Elita; Arsyadani Mishbahuddin (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2024)
The purpose of this study is to determine the effect of group counseling services on behavior contract techniques to improve the learning discipline of class XI social studies students at SMA Negeri 2 Bengkulu City. Researchers used the quantitative research one-group pretest-postest experimental method. The research subjects amounted to seven students who had low learning discipline. Data collection techniques include using learning discipline questionnaires. Data analysis techniques using t-Test. The results of this study showed the average score of learning discipline before being given treatment which was in the low category and after being given treatment into a very high category. The results of the t-test showed a value of t = -11.006 and sig (2-tailed) 0.000 (0.000<0.05), meaning that there was a significant influence on group counseling services behavior contract techniques to improve learning discipline in grade XI social studies students of SMA Negeri 2 Bengkulu City. Based on the results of the study, it is recommended that guidance and counseling teachers be able to use group counseling services with behavior contract techniques to improve learning discipline in students. Keywords: group counseling, learning discipline, behavior contract